La peinture de paysage traditionnelle chinoise Séjour dans les monts Fuchun et son influence sur la conception de projets paysagers contemporains dans la vallée du fleuve Qiantang (Chine) - Xuewu Dou; Aude Nuscia Taïbi; Mustapha El Hannani (Projets de Paysage)
Dwelling in the Fuchun Mountains is a traditional Chinese landscape painting by Huang Gongwang (1269-1354) that depicts the landscapes on both banks of the Fuchun River, one of the ten most famous landscapes in China. An examination of the work and of its philosophical message provides insight into its standing as a major work of Chinese art and the reasons why it has served as inspiration for countless urban and rural development projects in the area it depicts, as well as in other areas in China. The Fuchun River and its surrounding mountains, painted by Huang Gongwang over 670 years ago, is situated in the middle section of the Qiantang River, a cradle of Chinese civilisation and an area with several UNESCO World Heritage Sites recognised for their living cultural landscapes. This is a picturesque river made famous in China by the many paintings and major literary works in praise of it. This very rich cultural and historical landscape heritage which has been recognised for centuries is currently subjected to major transformations (urbanisation, agricultural development and the installation of dykes). This study focusing on several projects seeks to understand how current landscape developments are contributing to restoring harmony between inhabitants and nature by drawing inspiration from the harmony represented in Dwelling in the Fuchun Mountains.